PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Yuli Afrini Yuli Afrini; Sisri Wahyuni; Cindy Fadila; Dini Nurhidayah; Utari Ramadhani; Fachriza Setiawan; Disa Amelia Putri; Dea Angelica Putri; Sindi Rara Meris; Refa Oktalin Fitri; Fatma kholiza; Syantia Ardianti; Sulastri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the use of interactive learning media in mathematics learning in elementary schools. The research method used was a systematic literature review. The analysis results indicate that the use of interactive learning media such as digital applications, augmented reality, educational games, and manipulative media significantly improves students' understanding of mathematical concepts, motivation, and learning outcomes. Furthermore, interactive media has proven effective in creating enjoyable, contextual, and student centered learning environments. These findings confirm that interactive learning media not only facilitate conceptual understanding but also strengthen students' critical thinking, problem-solving skills, and positive attitudes toward mathematics in the 21st century. It is concluded that interactive learning media is an effective strategy for improving the quality of elementary mathematics education through innovative and technology-integrated learning.